2021
DOI: 10.21037/tp-20-264
|View full text |Cite
|
Sign up to set email alerts
|

Twin to twin transfusion syndrome

Abstract: Twin to twin transfusion syndrome (TTTS) is a common complication that typically presents in the second trimester of pregnancy in 10-15% of monochorionic twins due to net transfer of volume and hormonal substances from one twin to the other across vascular anastomoses on the placenta. Without recognition and treatment, TTTS is the greatest contributor to fetal loss prior to viability in 90-100% of advanced cases. Ultrasound diagnosis of monochorionicity is most reliable in the first trimester and sets the moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 107 publications
0
33
2
2
Order By: Relevance
“…This study showed the incidence of TTTS was 5.3% (1/19) in EM group and 0% in FR group. This seems somewhat lower than the 8%–17.6% and 10%–15% that was previously reported in MCTA triplets and MCDA twins respectively, 11,18,19 which need further large sample and collaborative evaluation in the future. A recent systematic review about the perinatal outcome after fetoscopic laser surgery for TTTS in 22 MCTA triplets revealed that all three fetuses survived in 48.4% of the pregnancies and at least one triplet survived in 88.9% pregnancies, indicating that this technique is feasible for treatment of this condition 20 .…”
Section: Discussioncontrasting
confidence: 64%
“…This study showed the incidence of TTTS was 5.3% (1/19) in EM group and 0% in FR group. This seems somewhat lower than the 8%–17.6% and 10%–15% that was previously reported in MCTA triplets and MCDA twins respectively, 11,18,19 which need further large sample and collaborative evaluation in the future. A recent systematic review about the perinatal outcome after fetoscopic laser surgery for TTTS in 22 MCTA triplets revealed that all three fetuses survived in 48.4% of the pregnancies and at least one triplet survived in 88.9% pregnancies, indicating that this technique is feasible for treatment of this condition 20 .…”
Section: Discussioncontrasting
confidence: 64%
“…Accordingly, any intervention that leads to at least one alive twin is considered as a clinical success. 1 , 2 Review of the published outcome of managed TTTS pregnancies revealed an overall success of live twins in the range of 53–78% 5 9 post-AR 29 , 36 , 42 , 43 and 50–88% post-FLA. 8 10 , 13 This study with the controlled AR protocol demonstrated an impressive overall success with 86% survival of the twins beyond 6 months of age. The best way for classification and management of twin pregnancies is currently still debated with significant global variations.…”
Section: Discussionmentioning
confidence: 99%
“…Twin-to-twin transfusion syndrome (TTTS) is a complication in monochorionic diamniotic (MCDA) twins in which blood is transferred from a donor to a recipient twin via anastomoses in the shared placenta. 1 The TTTS occurs only in 10–15% of MCDA pregnancies; however, if untreated, the expected perinatal morbidity and mortality is extremely high. 2 Historically, the placenta anastomoses have been well described since the mid-19th century, but intervention procedures were reported only in the late 1970’s.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations